Struktur Komunitas Gastropoda di Kawasan Mangrove Desa Batu Ampar Kalimantan Barat - Cahyany, Brigita Sari Kusuma; Alif, Daffa Pandya; Rahmadini, Nadilla; Triono, Riski; Fahreza, Hauri; Orchita, Hilaria; Simanjuntak, Retina; Ikhsan, Adjie Maulana; Alhajj, Muhammad Egy; Penemu, Yogie Aditya Bisi; Kushadiwijayanto, Arie Antasari (Oseanologia, 2025)
Batu Ampar Village is a coastal area included in the administrative area of Batu Ampar District, Kubu Raya Regency. The mangrove area of Batu Ampar Village reaches 58,953 ha and is a habitat for gastropods. Gastropods are a group of shelled animals that inhabit the mangrove area. The use of mangrove wood as charcoal in Batu Ampar Village causes damage and affects the life of gastropods. This study aims to examine the structure of the gastropod community in the mangrove area of Batu Ampar Village. The study was conducted on October 26, 2024 using a 1 x 1 m transect with a purposive random sampling method. Based on the results of gastropod identification in the mangrove area of Batu Ampar Village, West Kalimantan, 5 gastropod families were found consisting of Littorinidae, Muricidae, Ellobiidae, Potamididae, and Neritidae. The most commonly found species is Nerita balteata with a total density of 4 ind/m2. The diversity index (H"™) of gastropods is 0.73 and is classified as low. The gastropod uniformity index (E) is 0.59 and is classified as moderate. The gastropod dominance index (C) is 0.4 so that no species dominates.